Proteolytic cascade in the amyloidogenesis of Alzheimer's disease. (1st February 2004) - Sidera, C.; Parsons, R.; Austen, B.
Abstract : β-Amyloid, a neurotoxic peptide deposited in the brains of Alzheimer's disease patients, is released by a series of membrane-limited proteolytic events. β-Secretase activity is enhanced by cellular targeting into intracellular cholesterol-rich microdomains, which are dispersed by statins.